Fetal membranes: Potential source of preterm birth biomarkers - Menon, Ramkumar; Nicolau, Nathalia Noda [UNESP]; Bredson, Sarah; Polettini, Jossimara (Springer Nature, 2015)
Preterm birth (birth before 37 weeks of complete gestation) is a major pregnancy complication and is the second largest cause of neonatal mortality worldwide. Majority of the preterm births are due to unknown etiologies, and this class of preterm births is known as spontaneous preterm birth (PTB). There are no reliable biomarkers to predict PTB as its causality and pathophysiologic pathways are unclear. Various maternal and fetal intrauterine compartments produce biomarkers that are associated with PTB. However, screening and diagnosis of PTB is difficult due to the overlap between various pathologic events associated with PTB and heterogeneity in biomarker response. Several studies have contributed to our current understanding of the mechanistic role of biomarkers produced by maternal and fetal tissues, but none of them have emerged as diagnostic tools. This chapter reviews knowledge gaps in PTB biomarker literature and discusses some of the fundamental issues associated with biomarker research in PTB. This discussion is based on data generated using human fetal membranes. Fetal membranes (amniochorionic membranes) are fetally derived tissues and forms the innermost lining of the intra-amniotic cavity. They provide structural integrity to the intrauterine cavity and are capable of responding to various maternal-fetal physiologic and pathophysiologic signals. Reports document hundreds of biomarkers produced by fetal membranes that are associated with various pregnancy complications. However, fetal membrane biomarker response is complex, and the diversity in their response makes it difficult to understand the pathways of PTB. This chapter reviews three distinct scenarios where fetal membrane biomarker signature can vary: (1) type of antigen, (2) type of risk exposure, and (3) the race/ethnicity of the subject from which the membranes are derived. This is to highlight the heterogeneity in fetal membrane biomarkers and demonstrate how pathways can be different based on distinct biomarker signature. Understanding both maternal and fetal biomarker response based on an individual's own risk profile is needed to tailor interventions to reduce the risk of PTB.